Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Kho..................wa.....................troi.....................thi......................lanh.................ret.......................ai........................tich..........................ung.....................ho........................minh.....................cho....................do....................lanh
a; [6.(- \(\dfrac{1}{3}\))3 - 3.(- \(\dfrac{1}{3}\) + 1)] - ( - \(\dfrac{1}{3}\) - 1)
= [6. \(\dfrac{-1}{3^3}\) - 3.\(\dfrac{2}{3}\)] - ( - \(\dfrac{1}{3}\) - \(\dfrac{3}{3}\))
= [\(\dfrac{-2}{9}\) - 2] + \(\dfrac{4}{3}\)
= [\(\dfrac{-2}{9}\) - \(\dfrac{18}{9}\)] + \(\dfrac{12}{9}\)
= - \(\dfrac{20}{9}\) + \(\dfrac{12}{9}\)
= \(\dfrac{-8}{9}\)
b; (63 + 3.62 + 33): 13
= (216 + 3.36 + 27) : 13
= (216 + 108 + 27): 13
= (324 + 27): 13
= 351 : 13
= 27
a: =>(3/2-2x):2/3=1/6
=>3/2-2x=1/6x2/3=2/18=1/9
=>2x=25/18
hay x=25/36
b: \(\Leftrightarrow2x-2x+\dfrac{5}{2}-2=x-\dfrac{1}{4}\)
=>x-1/4=1/2
=>x=3/4
c: \(\Leftrightarrow2x-\dfrac{2}{3}-\dfrac{1}{3}x+\dfrac{1}{4}x=0\)
=>23/12x=2/3
=>x=8/23
Bài 1:
- \(\dfrac{11}{2}x\) + 1 = \(\dfrac{1}{3}x-\dfrac{1}{4}\)
- \(\dfrac{11}{2}\)\(x\) - \(\dfrac{1}{3}\)\(x\) = - \(\dfrac{1}{4}\) - 1
-(\(\dfrac{33}{6}\) + \(\dfrac{2}{6}\))\(x\) = - \(\dfrac{5}{4}\)
- \(\dfrac{35}{6}\)\(x\) = - \(\dfrac{5}{4}\)
\(x=-\dfrac{5}{4}\) : (- \(\dfrac{35}{6}\))
\(x\) = \(\dfrac{3}{14}\)
Vậy \(x=\dfrac{3}{14}\)
Bài 2: 2\(x\) - \(\dfrac{2}{3}\) - 7\(x\) = \(\dfrac{3}{2}\) - 1
2\(x\) - 7\(x\) = \(\dfrac{3}{2}\) - 1 + \(\dfrac{2}{3}\)
- 5\(x\) = \(\dfrac{9}{6}\) - \(\dfrac{6}{6}\) + \(\dfrac{4}{6}\)
- 5\(x\) = \(\dfrac{7}{6}\)
\(x\) = \(\dfrac{7}{6}\) : (- 5)
\(x\) = - \(\dfrac{7}{30}\)
Vậy \(x=-\dfrac{7}{30}\)
\(\left|\frac{5}{-4}\right|-\left|\frac{1}{-3}\right|+-\frac{5}{6}-4\frac{1}{2}\)
\(=\left|-\frac{5}{4}\right|-\left|\frac{-1}{3}\right|+\frac{-5}{6}-\frac{9}{2}\)
\(=\frac{5}{4}-\frac{1}{3}+\frac{-5}{6}-\frac{9}{2}=-\frac{53}{12}\)
\(\frac{5}{8}-\left|-\frac{1}{12}\right|-3\frac{1}{4}+\left|-\frac{5}{6}\right|\)
\(=\frac{5}{8}-\frac{1}{12}-\frac{13}{4}+\frac{5}{6}=-\frac{15}{8}\)
\(\frac{3}{-7}+\left|-\frac{5}{12}\right|+3\frac{1}{4}+\left|-\frac{5}{6}\right|\)
\(=\frac{-3}{7}+\frac{5}{12}+\frac{13}{4}+\frac{5}{6}=\frac{57}{14}\)
\(1\frac{3}{5}-\left|\frac{1}{-4}\right|+\frac{2}{-3}-\left|-\frac{1}{2}\right|\)
\(=\frac{8}{5}-\left|\frac{-1}{4}\right|+\frac{-2}{3}-\frac{1}{2}\)
\(=\frac{8}{5}-\frac{1}{4}+\frac{-2}{3}-\frac{1}{2}\)
\(=\frac{27}{20}+\frac{-7}{6}=\frac{27}{20}-\frac{7}{6}=\frac{11}{60}\)